Creep-resistant Bi-In-Sn fusible alloy foil and preparation method and application thereof

By introducing metal fiber mesh and RE elements into Bi-In-Sn fusible alloy foil, a three-layer sandwich structure is formed, which solves the problem of poor reliability of Bi-In-Sn fusible alloy in high-temperature service, and significantly improves the alloy foil The strength and toughness delay the high temperature creep of brass components.

CN119427852AActive Publication Date: 2025-02-14SUZHOU NUCLEAR POWER RES INST CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411609033.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Bi-In-Sn fusible alloys have poor reliability during high-temperature service, resulting in brass temperature-controlled components being prone to creep failure during brazing.

Method used

The creep-resistant Bi-In-Sn fusible alloy foil with a three-layer sandwich structure is Bi-In-Sn alloy inside, and the outer sides are covered by metal fiber mesh. The grain boundaries and refine structure are purified by adding RE elements. Improve the strength and toughness of the alloy.

Benefits of technology

It significantly improves the strength and toughness of the alloy foil, delays the high-temperature creep of brazed parts, and improves the strength and high-temperature service reliability of brazed joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119427852A_ABST
    Figure CN119427852A_ABST
Patent Text Reader

Abstract

The invention discloses a creep-resistant Bi-In-Sn fusible alloy foil which comprises an alloy sheet located in the alloy foil and a metal fiber net covering the surface of the alloy sheet, and the alloy sheet is a Bi-In-Sn alloy. According to the creep-resistant Bi-In-Sn fusible alloy foil, the fusible alloy is coated with the metal fiber net, and the fusible alloy plate is fixed and bound, so that the cracking risk of the alloy plate in the subsequent rolling process is inhibited, and the yield of the foil-shaped alloy is improved; secondly, the strength and the toughness of the alloy foil body are enhanced by the metal fiber net, and the alloy foil is not easy to crack in use and transportation processes; thirdly, when the brass temperature control component is brazed, the metal fiber net can be partially dissolved into a brazing seam, the solid solution strengthening effect is achieved, and high-temperature creep deformation of the component is delayed to a certain degree; and meanwhile, the metal fiber net which is not molten plays a role in pinning the deformation of the component in the brazing seam, so that the creep resistance of the component is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing materials, and in particular to a creep-resistant Bi-In-Sn fusible alloy foil, a preparation method of the creep-resistant Bi-In-Sn fusible alloy foil, and application of the creep-resistant Bi-In-Sn fusible alloy foil in brazing of brass parts. Background Art

[0002] Bi-In-Sn fusible alloy is a lead-free soft solder with a low melting temperature of about 85-90°C, good flowability and wetting properties, and has unique applications in the fields of automobiles, aviation, electrical instruments, light industry, etc.

[0003] However, since the Bi-In-Sn fusible alloy is mainly composed of a large number of brittle phases, such as BiIn phase and InSn4 phase, the brazing material is brittle and has low strength. Therefore, the processing performance of the fusible alloy is poor, and it is difficult to make it into foil or sheet by conventional methods, which limits the application of the alloy. In particular, when the fusible alloy is used for brazing brass temperature control components, due to the poor high-temperature service reliability of the fusible alloy, it is easy to cause creep failure of the components.

[0004] In order to solve the above-mentioned deficiencies, it is necessary to develop a creep-resistant Bi-In-Sn fusible alloy foil, which can not only improve the strength and toughness of the alloy foil itself, but also improve the strength and high-temperature service reliability of the brazed joints of the brass temperature control components. Summary of the invention

[0005] In view of this, in order to overcome the defects of the prior art and achieve the above-mentioned purpose, the present invention provides a creep-resistant Bi-In-Sn fusible alloy foil.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A creep-resistant Bi-In-Sn fusible alloy foil comprises an alloy sheet located inside and a metal fiber mesh covering a part of the surface area of ​​the alloy sheet, wherein the alloy sheet is a Bi-In-Sn alloy. That is, the creep-resistant Bi-In-Sn fusible alloy foil is a three-layer sandwich structure, wherein the interior is a Bi-In-Sn alloy and both sides of the exterior are covered by metal fiber meshes.

[0008] According to some preferred embodiments of the present invention, the metal fiber mesh is formed by fiber filaments wound on the surface of the alloy sheet, and the spacing between adjacent fiber filaments is 3-5 mm.

[0009] According to some preferred embodiments of the present invention, the diameter of the fiber filament is 100-500 um.

[0010] According to some preferred embodiments of the present invention, the fiber filaments are made of one or more of silver, nickel or copper.

[0011] According to some preferred implementation aspects of the present invention, the mass fractions of each element in the Bi-In-Sn alloy are: Bi56-60 parts, In 25-28 parts, Sn 12-15 parts, RE 0.1-0.5 parts. Adding an appropriate amount of RE (mixed rare earth) elements to the Bi-In-Sn alloy plays a role in purifying the grain boundary and refining the structure, further improving the strength and toughness of the solder body.

[0012] According to some preferred embodiments of the present invention, the RE is one or more of Ce, Sc, and Nd.

[0013] According to some preferred implementation aspects of the present invention, the fusible alloy foil is formed by winding fiber filaments around an alloy plate and rolling the alloy plate, the alloy plate forms an alloy sheet, and the fiber filaments form a metal fiber mesh.

[0014] According to some preferred implementation aspects of the present invention, the thickness of the alloy plate before rolling is 1.5-2 mm, and the thickness of the fusible alloy foil formed after rolling is 0.1-0.5 mm, that is, the fusible alloy after rolling is in foil form.

[0015] According to some preferred implementation aspects of the present invention, after rolling, the surface of the alloy sheet has a groove for accommodating the metal fiber mesh, and the metal fiber mesh is located in the groove.

[0016] According to some preferred implementation aspects of the present invention, after rolling, the surface of the metal fiber mesh is flush with the surface of the alloy sheet.

[0017] The present invention also provides a method for preparing the above-mentioned creep-resistant Bi-In-Sn fusible alloy foil, comprising the following steps:

[0018] On the outer surface of the alloy plate, fiber wires are wound and coated at equal intervals along the length direction thereof; the alloy plate is rolled to a finished thickness to form an alloy sheet, and the fiber wires are formed into a metal fiber mesh to obtain a creep-resistant Bi-In-Sn fusible alloy foil.

[0019] According to some preferred implementation aspects of the present invention, during rolling, the alloy plate with fiber filaments wound around its surface is immersed in an oil bath at a temperature of 50-70°C.

[0020] According to some preferred implementation aspects of the present invention, the alloy plate is prepared by the following steps: heating and melting the Bi-In-Sn alloy raw material into molten metal; injecting the molten metal into a mold cavity, and obtaining the alloy plate after cooling and demolding.

[0021] According to some preferred implementation aspects of the present invention, the surface of the mold cavity is coated with mold release oil, and the mold release oil is one or more of soybean oil, peanut oil, and rapeseed oil.

[0022] Specifically, in some embodiments of the present invention, the method for preparing the creep-resistant Bi-In-Sn fusible alloy foil comprises the following steps:

[0023] Step 1: Prepare Bi-In-Sn alloy raw materials according to mass fractions, place the raw materials inside the graphite crucible of a high-frequency induction welding machine, heat to 90-150° C., and melt into molten metal for standby use.

[0024] Step 2: First, evenly apply the demoulding oil on the inner surface of the graphite mold, and then assemble and fix it. The demoulding oil is one or more of soybean oil, peanut oil, and rapeseed oil.

[0025] Step 3: inject the molten metal from step 1 into the graphite mold cavity assembled in step 2, and after cooling and demolding, obtain an alloy plate with a thickness of 1.5 to 2 mm.

[0026] Step 4: Wind and coat the alloy plate prepared in step 3 with metal fiber wires at equal intervals (3-5 mm) along its length, and then roll it to the finished thickness by placing the rollers and the brazing plate (alloy plate) in an oil bath at 50-70°C using a rolling mill to obtain a creep-resistant fusible alloy foil.

[0027] The present invention also provides an application of the creep-resistant Bi-In-Sn fusible alloy foil in brazing of brass parts.

[0028] Due to the adoption of the above technical scheme, compared with the prior art, the advantages of the present invention are as follows: the creep-resistant Bi-In-Sn fusible alloy foil of the present invention adopts a metal fiber mesh coated on the outside of the fusible alloy, firstly, the fusible alloy plate is fixed, thereby suppressing the risk of cracking of the alloy plate during subsequent rolling and improving the yield of the foil-like alloy; secondly, the metal fiber mesh enhances the strength and toughness of the alloy foil body, and is not easy to crack during use and transportation; thirdly, when brazing the brass temperature control component, the metal fiber mesh will partially dissolve into the brazing seam, play a role of solid solution strengthening, and delay the high-temperature creep of the component to a certain extent; at the same time, the unmelted metal fiber mesh plays a role of pinning the component deformation in the brazing seam, thereby significantly improving the anti-creep performance of the component. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 A schematic diagram of the cross-sectional structure of a creep-resistant Bi-In-Sn fusible alloy foil in a preferred embodiment of the present invention;

[0031] Figure 2 This is a schematic diagram of the structure of fiber filaments wound around an alloy plate in a preferred embodiment of the present invention (before rolling);

[0032] Figure 3 An enlarged view of the creep-resistant Bi-In-Sn fusible alloy foil in a preferred embodiment of the present invention (after rolling);

[0033] Figure 4 This is a photo of the shear sample of the alloy foil brazed brass joint prepared in Experimental Example 2 of the present invention;

[0034] Figure 5 This is a photo of the brass temperature control component prepared in Experimental Example 3 of the present invention.

[0035] In the accompanying drawings, 1-metal fiber mesh, 2-alloy sheet. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0037] The creep-resistant Bi-In-Sn fusible alloy foil of the present invention can not only improve the strength and toughness of the alloy foil itself, but also improve the strength and high-temperature service reliability of the brazed joint of the brass temperature control component; at the same time, a preparation method of the alloy foil is provided to achieve the preparation of the Bi-In-Sn fusible alloy foil. The details are as follows:

[0038] The creep-resistant Bi-In-Sn fusible alloy foil of this embodiment includes an alloy sheet 2 (solder) located inside and a metal fiber mesh 1 covering the surface of the alloy sheet, and the alloy sheet is a Bi-In-Sn alloy. The mass fractions of each element in the Bi-In-Sn alloy are: Bi 56-60 parts, In 25-28 parts, Sn 12-15 parts, and RE 0.1-0.5 parts. RE is one or more of Ce, Sc, and Nd. Adding an appropriate amount of RE elements to the Bi-In-Sn alloy plays a role in purifying the grain boundaries and refining the structure, further improving the strength and toughness of the solder body.

[0039] That is, the creep-resistant Bi-In-Sn fusible alloy foil of this embodiment is a three-layer sandwich structure, with the interior being Bi-In-Sn alloy and the exterior being partially covered on both sides by metal fiber mesh.

[0040] The metal fiber mesh is formed by fiber filaments wound on the surface of the alloy sheet, and the spacing between adjacent fiber filaments is 3-5mm. The diameter of the fiber filaments is 100-500um. The material of the fiber filaments is one or more of silver, nickel or copper.

[0041] The fusible alloy foil is formed by winding fiber filaments around the alloy plate and rolling. The alloy plate forms an alloy sheet, and the fiber filaments form a metal fiber mesh. The thickness of the alloy plate before rolling is 1.5-2 mm, and the thickness of the fusible alloy foil formed after rolling is 0.1-0.5 mm. That is, the fusible alloy after rolling is in the form of foil. After rolling, the surface of the alloy sheet has a groove for accommodating the metal fiber mesh, and the metal fiber mesh is located in the groove. After rolling, the surface of the metal fiber mesh is flush with the surface of the alloy sheet.

[0042] The method for preparing the creep-resistant Bi-In-Sn fusible alloy foil of this embodiment comprises the following steps:

[0043] Step 1: Prepare Bi-In-Sn alloy raw materials according to mass fractions, place the raw materials inside the graphite crucible of a high-frequency induction welding machine, heat to 90-150° C., and melt into molten metal for standby use.

[0044] Step 2: Apply mold release oil evenly on the inner surface of the graphite mold, and then assemble and fix it. The mold release oil is one or more of soybean oil, peanut oil, and rapeseed oil.

[0045] Step 3: inject the molten metal from step 1 into the graphite mold cavity assembled in step 2, and after cooling and demolding, obtain an alloy plate with a thickness of 1.5 to 2 mm.

[0046] Step 4: Wind and coat the alloy plate prepared in step 3 with metal fiber wires at equal intervals (3-5 mm) along its length, and then use a rolling mill, with the rollers and the brazing plate (alloy plate) placed in an oil bath at a temperature of 50-70°C, to roll the alloy plate to form an alloy sheet, and the fiber wires to form a metal fiber mesh, to obtain a creep-resistant Bi-In-Sn fusible alloy foil.

[0047] Example 1

[0048] The creep-resistant Bi-In-Sn fusible alloy foil of this embodiment includes an alloy sheet (solder) located inside and a metal fiber mesh covering the surface of the alloy sheet, and the alloy sheet is a Bi-In-Sn alloy. The mass fractions of each element in the Bi-In-Sn alloy are: 56 parts of Bi, 25 parts of In, 12 parts of Sn, and 0.1 parts of RE. RE is Ce. Adding an appropriate amount of RE element to the Bi-In-Sn alloy plays a role in purifying the grain boundary and refining the structure, further improving the strength and toughness of the solder body.

[0049] That is, the creep-resistant Bi-In-Sn fusible alloy foil of this embodiment is a three-layer sandwich structure, with the interior being Bi-In-Sn alloy and the exterior being covered by metal fiber mesh on both sides.

[0050] The metal fiber mesh is formed by fiber filaments wound on the surface of the alloy sheet, the spacing between adjacent fiber filaments is 3mm, the diameter of the fiber filaments is 100um, and the material of the fiber filaments is silver.

[0051] The fusible alloy foil is formed by winding fiber filaments around the alloy plate and rolling. The alloy plate forms an alloy sheet, and the fiber filaments form a metal fiber mesh. The thickness of the alloy plate before rolling is 1.5 mm, and the thickness of the fusible alloy foil formed after rolling is 0.1 mm. That is, the fusible alloy after rolling is in the form of foil. After rolling, the surface of the alloy sheet has a groove for accommodating the metal fiber mesh, and the metal fiber mesh is located in the groove. After rolling, the surface of the metal fiber mesh is flush with the surface of the alloy sheet.

[0052] The method for preparing the creep-resistant Bi-In-Sn fusible alloy foil of this embodiment comprises the following steps:

[0053] Step 1: Prepare Bi-In-Sn alloy raw materials according to mass fractions, place the raw materials in a graphite crucible of a high-frequency induction welding machine, heat to 90° C., and melt into molten metal for later use.

[0054] Step 2: First, apply the mold release oil evenly on the inner surface of the graphite mold, and then assemble and fix it. The mold release oil is soybean oil.

[0055] Step 3: Inject the molten metal from step 1 into the graphite mold cavity assembled in step 2, and after cooling and demolding, obtain an alloy plate with a thickness of 1.5 mm.

[0056] Step 4: Wind and coat the alloy plate prepared in step 3 with metal fiber wires at equal intervals (3 mm) along its length, and then use a rolling mill, with the rollers and the brazing plate (alloy plate) placed in an oil bath at 50°C, to roll the plate to the finished thickness, forming an alloy sheet and a metal fiber mesh to obtain a creep-resistant Bi-In-Sn fusible alloy foil.

[0057] Example 2

[0058] The structure and preparation method of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are basically the same as those in Embodiment 1, except that:

[0059] The mass fractions of the elements in the alloy sheet (solder) of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are: Bi57, In26, Sn13, RE 0.2; RE is Sc.

[0060] The fiber wire is made of nickel, and the spacing between adjacent fiber wires is 3.5 mm. The diameter of the fiber wire is 200 um. The thickness of the alloy plate before rolling is 1.6 mm, and the thickness of the fusible alloy foil formed after rolling is 0.2 mm.

[0061] The temperature when heating the Bi-In-Sn alloy raw material to melt into molten metal is 100°C; the demoulding oil is peanut oil; and the oil bath temperature during rolling is 60°C.

[0062] Example 3

[0063] The structure and preparation method of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are basically the same as those in Embodiment 1, except that:

[0064] The mass fractions of the elements in the alloy sheet (solder) of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are: Bi58, In27, Sn14, RE 0.3; RE is Nd.

[0065] The fiber wire is made of copper, and the spacing between adjacent fiber wires is 4 mm. The diameter of the fiber wire is 300 um. The thickness of the alloy plate before rolling is 1.8 mm, and the thickness of the fusible alloy foil formed after rolling is 0.3 mm.

[0066] The temperature when heating the Bi-In-Sn alloy raw material to melt into molten metal is 110°C; the demoulding oil is rapeseed oil; and the oil bath temperature during rolling is 65°C.

[0067] Example 4

[0068] The structure and preparation method of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are basically the same as those in Embodiment 1, except that:

[0069] The mass fractions of the elements in the alloy sheet (solder) of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are: Bi59, In28, Sn15, RE 0.4; RE is Ce.

[0070] The fiber is made of silver, and the distance between adjacent fiber is 4.5mm. The diameter of the fiber is 400um. The thickness of the alloy plate before rolling is 1.9mm, and the thickness of the fusible alloy foil formed after rolling is 0.4mm.

[0071] The temperature when heating the Bi-In-Sn alloy raw material to melt into molten metal is 120°C; the demoulding oil is soybean oil; and the oil bath temperature during rolling is 70°C.

[0072] Example 5

[0073] The structure and preparation method of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are basically the same as those in Embodiment 1, except that:

[0074] The mass fractions of the elements in the alloy sheet (solder) of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are: Bi60, In28, Sn15, RE 0.5; RE is Ce.

[0075] The fiber is made of silver, and the distance between adjacent fiber is 5 mm. The diameter of the fiber is 500 um. The thickness of the alloy plate before rolling is 2 mm, and the thickness of the fusible alloy foil formed after rolling is 0.5 mm.

[0076] The temperature when heating the Bi-In-Sn alloy raw material to melt into molten metal is 130°C; the demoulding oil is soybean oil; and the oil bath temperature during rolling is 70°C.

[0077] Example 6

[0078] The structure and preparation method of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are basically the same as those in Embodiment 1, except that:

[0079] The mass fractions of the elements in the alloy sheet (solder) of the creep-resistant Bi-In-Sn fusible alloy foil in this embodiment are: Bi60, In28, Sn15, RE 0.5; RE is Sc.

[0080] The fiber wire is made of nickel, and the spacing between adjacent fiber wires is 5 mm. The diameter of the fiber wire is 500 um. The thickness of the alloy plate before rolling is 2 mm, and the thickness of the fusible alloy foil formed after rolling is 0.5 mm.

[0081] The temperature when heating the Bi-In-Sn alloy raw material to melt into molten metal is 150°C; the demoulding oil is soybean oil; and the oil bath temperature during rolling is 70°C.

[0082] Comparative Example 1

[0083] The Bi-In-Sn fusible alloy foil in this comparative example only has an alloy sheet similar to that in Example 1, but no metal fiber mesh covering the outer surface of the alloy sheet. The composition and preparation method of the alloy sheet are basically the same as those in Example 1.

[0084] Comparative Example 2

[0085] The structure and preparation method of the Bi-In-Sn fusible alloy foil of this comparative example are basically the same as those of Example 1, except that: in the alloy sheet of the Bi-In-Sn fusible alloy foil of this comparative example, the Bi-In-Sn alloy does not contain RE components.

[0086] Comparative Example 3

[0087] The structure and preparation method of the Bi-In-Sn fusible alloy foil in this comparative example are basically the same as those in Example 1, except that the spacing between adjacent fiber filaments of the metal fiber mesh on the Bi-In-Sn fusible alloy foil in this comparative example is greater than 5 mm, that is, 8 mm.

[0088] Comparative Example 4

[0089] The structure and preparation method of the Bi-In-Sn fusible alloy foil in this comparative example are basically the same as those in Example 1, except that the spacing between adjacent fiber filaments of the metal fiber mesh on the Bi-In-Sn fusible alloy foil in this comparative example is less than 3 mm, which is 1 mm.

[0090] Tests and Results

[0091] Experimental Example 1

[0092] In order to examine and compare the forming properties of the alloy foils in Examples 1-6 of the present invention and Comparative Examples 1-4, 1 kg of solder alloy foil was prepared according to the preparation methods in Examples 1-6 and Comparative Examples 1-4, respectively.

[0093] By comparison, it is found that Examples 1-6 can obtain ideal creep-resistant fusible alloy foils with a yield rate of more than 80%, while the composition of Comparative Example 1 is relatively brittle, there is no external metal fiber fixing and shaping rolling, the formability is poor, and no solder foil can be obtained; the toughness of Comparative Example 2 is slightly better, and a solder foil can be obtained, but the Bi-In-Sn alloy does not contain RE components, and the solder foil has coarse grains and low strength; in Comparative Example 3, the metal fiber filaments are relatively large in spacing, and an alloy foil can be obtained, but the yield rate is low, about 35%; Comparative Example 4 can obtain a solder foil, but the metal fibers on the outside of the solder foil are densely arranged, which affects the performance of the brazing joint, the fiber web is dense, the fiber ratio is high, and the proportion of fusible alloy components is small, and effective brazing cannot be achieved.

[0094] Experimental Example 2

[0095] In order to investigate and compare the shear strength of brazed joints of alloy foils in Examples 1-6 of the present invention and Comparative Examples 1-4, induction brazing tests of brass plates were carried out using 10 kinds of brazing alloy foils in Examples 1-6 and Comparative Examples 1-4, and then the shear strength test of the joints was carried out according to the requirements of GB / T 11363. The test results are shown in Table 1 below.

[0096] Table 1 Shear strength of brass plate joints

[0097] Brazing material type Average shear strength of joints / MPa Example 1 26.4 Example 2 27.8 Example 3 31.2 Example 4 27.5 Example 5 26.3 Example 6 24.9 Comparative Example 1 16.5 Comparative Example 2 18.8 Comparative Example 3 20.2 Comparative Example 4 10.5

[0098] The results in Table 1 show that compared with Comparative Examples 1-4, the shear strength of the joints of the alloy foil brazed brass plates in the embodiments is significantly higher, especially in Example 3, where the shear strength of the joint is as high as 31.2 MPa.

[0099] Experimental Example 3

[0100] In order to investigate and compare the high temperature service performance of the alloy foil brazed brass temperature control components in Examples 1-6 of the present invention and the comparative example, high temperature tensile tests of different temperature control components were carried out in accordance with the provisions of GB / T 11363 (test conditions were 45±2°C, loading 1000±2N, and load holding for 5min), and the tensile creep displacement of the components under the same conditions was measured. The experimental results are shown in Table 2 below.

[0101] Table 2 Load-keeping tensile creep displacement of brass plate joints

[0102] Brazing material type Initial sample length mm Length of sample after holding load for 5 minutes / mm Creep displacement / mm Example 1 66.96 67.10 0.14 Example 2 68.78 68.90 0.12 Example 3 67.10 67.20 0.10 Example 4 66.60 66.60 0.00 Example 5 66.50 66.65 0.15 Example 6 66.80 66.89 0.09 Comparative Example 1 66.85 67.69 0.84 Comparative Example 2 66.90 67.55 0.65 Comparative Example 3 66.78 67.28 0.50 Comparative Example 4 68.80 70.00 1.20

[0103] The results in Table 2 show that the creep displacement of the temperature control components of Examples 1-6 during high temperature service is much less than 0.5 mm, while the creep displacement of the temperature control components of Comparative Examples 1-4 during high temperature service is greater than or equal to 0.5 mm. It can be seen that the creep resistance of the brass temperature control components brazed by the fusible alloy in the examples is significantly better.

[0104] The present invention coats the surface of the Bi-In-Sn alloy with a metal fiber mesh, thereby improving the strength and toughness of the alloy foil body; by adding an appropriate amount of RE elements, the grain boundaries are purified and the structure is refined, further improving the strength and toughness of the solder body; to obtain the solder foil, the present invention fixes the fusible alloy plate with metal fibers, and then performs oil bath warm rolling to achieve the preparation of Bi-In-Sn fusible alloy foil with a high yield rate. Compared with the prior art, the present invention has the following beneficial effects:

[0105] (1) The metal fiber mesh coated with the fusible alloy of the present invention has three advantages: first, the fusible alloy plate is fixed, which suppresses the risk of cracking of the alloy plate during the subsequent rolling process and improves the yield rate of the foil alloy; second, the metal fiber mesh enhances the strength and toughness of the alloy foil body, which is not easy to crack during use and transportation; third, when brazing the brass temperature control component, the metal fiber mesh will partially dissolve into the brazing seam, play a role of solid solution strengthening, and delay the high-temperature creep of the component to a certain extent; at the same time, the unmelted metal fiber mesh plays a role of pinning the deformation of the component in the brazing seam, which significantly improves the anti-creep performance of the component;

[0106] (2) The Bi-In-Sn alloy of the present invention contains a trace amount of Re element, which plays a role in purifying the grain boundaries and refining the grains, further improving the strength and toughness of the alloy body and improving the creep resistance;

[0107] (3) The present invention realizes the effective preparation of creep-resistant Bi-In-Sn fusible alloy foil through the processing technology of alloy plate casting, alloy plate winding metal fiber solidification, and oil bath warm rolling.

[0108] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A creep-resistant Bi-In-Sn fusible alloy foil, characterized in that: The invention comprises an alloy sheet located inside and a metal fiber mesh covering the surface of the alloy sheet, wherein the alloy sheet is a Bi-In-Sn alloy; the metal fiber mesh is formed by fiber filaments wound on the surface of the alloy sheet, and the spacing between adjacent fiber filaments is 3-5 mm; the mass fractions of each element in the Bi-In-Sn alloy are: 56-60 parts of Bi, 25-28 parts of In, 12-15 parts of Sn, and 0.1-0.5 parts of RE; the fusible alloy foil is formed by winding fiber filaments outside the alloy plate and rolling, the alloy plate forms the alloy sheet, and the fiber filaments form the metal fiber mesh.

2. The creep-resistant Bi-In-Sn fusible alloy foil according to claim 1, characterized in that: The diameter of the fiber filament is 100-500um.

3. The creep-resistant Bi-In-Sn fusible alloy foil according to claim 1, characterized in that: The fiber filaments are made of one or more of silver, nickel or copper.

4. The creep-resistant Bi-In-Sn fusible alloy foil according to claim 1, characterized in that: The RE is one or more of Ce, Sc, and Nd.

5. The creep-resistant Bi-In-Sn fusible alloy foil according to claim 1, characterized in that: The thickness of the alloy plate before rolling is 1.5-2 mm, and the thickness of the fusible alloy foil formed after rolling is 0.1-0.5 mm.

6. The creep-resistant Bi-In-Sn fusible alloy foil according to claim 5, characterized in that: After rolling, the surface of the alloy sheet has a groove for accommodating the metal fiber mesh, and the metal fiber mesh is located in the groove; after rolling, the surface of the metal fiber mesh is flush with the surface of the alloy sheet.

7. A method for preparing a creep-resistant Bi-In-Sn fusible alloy foil, characterized in that: The steps include: On the outer surface of the Bi-In-Sn alloy plate, fiber filaments are wound and coated at equal intervals along its length direction; after rolling to the finished thickness, the alloy plate forms an alloy sheet, and the fiber filaments form a metal fiber mesh to obtain a creep-resistant Bi-In-Sn fusible alloy foil; during rolling, the alloy plate with the fiber filaments wound on the surface is immersed in an oil bath at a temperature of 50 to 70°C.

8. The preparation method according to claim 7, characterized in that: The alloy plate is prepared by the following steps: heating and melting Bi-In-Sn alloy raw materials into molten metal; injecting the molten metal into a mold cavity, and cooling and demolding to obtain the alloy plate.

9. The preparation method according to claim 8, characterized in that: The surface of the mold cavity is coated with mold release oil, and the mold release oil is one or more of soybean oil, peanut oil, and rapeseed oil.

10. Use of the creep-resistant Bi-In-Sn fusible alloy foil according to any one of claims 1 to 6 in brazing of brass parts.

Citation Information

Patent Citations

  • holding device for workpieces to be joined by soldering or welding

    AT164833B

  • Lead-free brazing filler metal, preparation method of lead-free brazing filler metal, application of lead-free brazing filler metal, brazing material profile and electronic component

    CN110303270A

  • Brazing filler metal alloy for photovoltaic welding strip as well as preparation method and application of brazing filler metal alloy

    CN114131238A

  • High-stability and high-reliability height-limiting type preformed soldering lug and preparation method thereof

    CN117066752A